Integrating Systems Thinking and Entrepreneurial Thinking : A Cognitive Perspective in Managing Corporate Turnaround - Nengah Rama Gautama; Pri Hermawan; Eko Agus Prasetio (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study explores the integration of Systems Thinking (ST) and Entrepreneurial Thinking (ET) as complementary cognitive frameworks to develop a comprehensive approach to effective corporate turnaround management. Traditional turnaround strategies often emphasize linear processes, such as retrenchment and restructuring, while overlooking corporate decline and recovery's cognitive dimensions and dynamic nature. By synthesizing insights from various theoretical perspectives—including Resource-Based Theory, Stage Theory, Cognitive-Behavioral Theory, and Political Behavior—this research proposes a cyclical model that recognizes four interconnected stages: Cognitive, Behavioral, Turnaround Outcome, and Learning. This model highlights how managerial cognition shapes strategic choices and implementation effectiveness throughout the turnaround process. Unlike conventional approaches, the framework of this study incorporates cognitive adaptation, feedback loops, and resilience-building elements to enhance organizational recovery and long-term sustainability. The study culminates in developing an Integrated Turnaround Strategy Canvas. This practical tool enables decision-makers to apply cognitive skills in assessing corporate decline, implementing practical recovery actions, and building adaptive capabilities. This research contributes to the turnaround literature by highlighting the importance of cognitive flexibility, holistic thinking, entrepreneurial innovation, and political engagement in navigating organizational crises, moving beyond cost-cutting measures to foster strategic agility and sustainable competitive advantage in volatile business environments.